89.0k views
1 vote
Please help me ASAP?!!

Please help me ASAP?!!-example-1
User Juve
by
5.3k points

2 Answers

1 vote

the answer 05 and 4 13

User Ramesh Kotkar
by
5.4k points
5 votes

Answer:

(0,-5) and (-4,3)

Explanation:

The given equations are


\left \{ {{x^2+y^2=25} \atop {2x+y=-5}} \right.

Make y the subject in the second equation;


y=-2x-5

Substitute into the first equation;


x^2+(-2x-5)^2=25

Expand:


x^2+4x^2+20x+25=25


x^2+4x^2+20x+25-25=0


5x^2+20x=0


5x(x+4)=0


\Rightarrow x=0,x=-4

When x=0,


y=-2(0)-5=-5

This gives; (0,-5)

When x=-4


y=-2(-4)-5=3

This gives (-4,3)

User Vervious
by
5.6k points